Cacat Mekanisme Pelaksanaan Revisi UU KPK 2019 dan Perbandingan Substansi serta Dampak Terhadap Kinerja KPK - Mohammad Zulfahmi; Rosalia Dika Agustanti (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2024)
This article examines the negative impact of the implementation of the revision of Law Number 19 of 2019 on the Corruption Eradication Commission (KPK) in Indonesia. The main focus is on a substantive comparison between the revised KPK Law and previous laws, highlighting significant changes in the KPK's leadership selection mechanism, authority and independence. This research also analyzes the impact of these revisions on the performance and performance of the Corruption Eradication Commission, including changes in organizational structure, transfer of authority, and the impact on handling corruption cases. This evaluation provides critical insight into these legal changes, with the hope of providing a better understanding of the challenges faced by the Corruption Eradication Commission in carrying out its crucial mission of eradicating corruption. These results can aim to identify errors in the formation of the revision of the Corruption Eradication Commission Law which was initiated in 2019 using a regulatory approach to the formation of legislation. This article was written normatively, namely a research method that focuses on the analysis of legal documents or literature as the main source. This method does not involve collecting primary data, but instead focuses on the study and interpretation of legal texts or related literature. These results are then closed with suggestions and recommendations given so that the revision of the Corruption Eradication Committee Law that has been attempted does not become an arbitrary legal instrument but remains a good implementation so as to create a climate of good governance for the legal atmosphere in Indonesia.